Screening methods in pharmacology - Parmar, N. S. (Alpha Science International Ltd, 2006)
The book provides an up-to-date and concise account of in vivo methods used in pharmacological screening of important categories of clinically useful drugs. Encompasses the basic principles of animal experimentation and current advances leading to the use of transgenic animals, combinatorial chemistry, high throughout screening pharmacogenomics, proteomics and array technology.